Identification and antimicrobial susceptibility of milk isolates from cows with subclinical mastitis in the northwest of Paraná State, Brazil - Ito Eleodoro, Josiane; Muraga, Luiza; Vanot, Rogério Luiz; Fagnani, Rafael (Veterinaria Italiana, 2023)
Bovine mastitis is a multifactorial disease, caused mainly by bacteria, whose most traditional method of treatment is the use of antibiotics. However, incorrect administration of these drugs may lead to the emergence of resistant strains. The objective of this study was to identify the most common pathogens causing subclinical mastitis in the northwest State of Paraná, Brazil and establish their antimicrobial susceptibility profiles. A total of 507 foremilk samples were collected in 13 municipalities. Bacteria were identified and their profile of antimicrobial susceptibility were tested. The distribution of positive samples was not homogeneous among the cities. Streptococci were the most frequently genus observed (61%), followed by staphylococci (28%) and other genera (11%). Among streptococci and staphylococci, Streptococcus uberis and Staphylococcus aureus were the most frequently identified species, respectively. Overall, 40% of the isolates showed resistance to at least one of the antibiotics used in this study. A high proportion of cefoperazone resistant Staphylococcus spp. and bacitracin resistant Streptococcus were observed. The isolated microorganisms showed little resistance to enrofloxaxin. The results obtained show the importance of isolating the microorganism causing mastitis and testing its resistance to antibiotics before performing the treatment of the disease.